Biocoating—A Critical Step Governing the Oral Delivery of Polymeric Nanoparticles. Issue 26 (23rd May 2022) - Azagury, Aharon; Baptista, Cameron; Milovanovic, Kosta; Shin, Hyeseon; Morello, Peter; Perez‐Rogers, James; Goldenshtein, Victoria; Nguyen, Travis; Markel, Arianna; Rege, Soham; Hojsak, Stephanie; Perl, Alexander; et al.
Abstract: Decades of research into the topic of oral nanoparticle (NP) delivery has still not provided a clear consensus regarding which properties produce an effective oral drug delivery system. The surface properties—charge and bioadhesiveness—as well as in vitro and in vivo correlation seem to generate the greatest number of disagreements within the field. Herein, a mechanism underlying the in vivo behavior of NPs is proposed, which bridges the gaps between these disagreements. The mechanism relies on the idea of biocoating—the coating of NPs with mucus—which alters their surface properties, and ultimately their systemic uptake. Utilizing this mechanism, several coated NPs are tested in vitro, ex vivo, and in vivo, and biocoating is found to affect NPs size, zeta‐potential, mucosal diffusion coefficient, the extent of aggregation, and in vivo/in vitro/ex vivo correlation. Based on these results, low molecular weight polylactic acid exhibits a 21‐fold increase in mucosal diffusion coefficient after precoating as compared to uncoated particles, as well as 20% less aggregation, and about 30% uptake to the blood in vivo. These discoveries suggest that biocoating reduces negative NP charge which results in an enhanced mucosal diffusion rate, increased gastrointestinal retention time, and high systemic uptake. Abstract : The mechanism underlying the in vivo behavior of nanoparticles (NPs) relies on the idea of biocoating—the coating of NPs with mucus—which alters their surface properties, mucosal diffusion coefficients and their extent of aggregation. These discoveries suggest that biocoating reduces negative NP charge which results in an enhanced mucosal diffusion rate, increased gastrointestinal retention time, and higher systemic uptake.